The Effect of Job Insecurity, Professional Identity, and Well-Being with Job Engagement Mediation Variables on Turnover Intention in State-Owned Enterprises (SOEs) Banks - Felicia Starryna; Aryana Satrya (Eduvest - Journal of Universal Studies, 2025)
This study aims to examine the influence of Job Insecurity, Professional Identity, and Well-being initiatives on Turnover Intention, with Job Engagement functioning as a mediating variable, within the context of State-Owned Enterprise (SOE) banks in Indonesia. Data were obtained through the administration of an online survey employing a 7-point Likert scale, and analyzed using Structural Equation Modeling (SEM) via LISREL 8.8 to test the proposed hypotheses. From the initial 463 collected responses, 265 valid responses were retained following a rigorous data screening and cleansing procedure. The empirical results indicate that Job Insecurity has a positive and significant direct effect on Turnover Intention, whereas Professional Identity and Well-being demonstrate positive and significant effects on Job Engagement. Moreover, Job Engagement fully mediates the relationship between Well-being and Turnover Intention, and partially mediates the effects of Job Insecurity and Professional Identity on Turnover Intention. These findings contribute to the growing body of knowledge in Human Resource Management by offering new insights into the mechanisms through which Job Insecurity, Professional Identity, and Well-being practices impact employee retention in the banking industry, with a particular focus on SOE institutions in emerging markets. The study underscores the strategic importance of fostering Job Engagement as a buffer against employees' intentions to leave the organization.